Demand-responsive Users’ Travel Behavior and Satisfaction Analysis in Small Cities: Case Study of the Public Transportation System in Palestine - Jaber, Ahmed; Al-Sahili, Khaled; Juhász, János (Periodica Polytechnica Transportation Engineering, 2023)
This study examines the differences in travel behavior between regular and occasional demand-responsive transport users (public transport users), determines the level of service satisfaction, and identifies the key factors of commuters’ preferences of using the demand-responsive transport regularly or occasionally for a small-sized urban area (<50 km2). Data were supplemented through field surveys and by focus group discussions. Binary logistic regression and correlation models were used. It is found that probabilities of irregularity are higher for rural areas, male commuters, short trips, educational trips, low-income groups, and non-direct trips. All users are generally satisfied with the service. The most important factors for occasional users are waiting time, trip cost, and trip duration. On the other hand, regular users pay more attention to cleanliness, safety, and comfort. Scheduling of public transportation lines that serve educational zones and provide accessibility to rural areas are needed to improve the quality and attractiveness of the services.